THE IMPACT OF 5TH INDUSTRIAL REVOLUTION TECHNOLOGIES ON ACADEMIC LIBRARIES: IMPROVING DIVERSITY AND INCLUSIVE SERVICES IN OPEN AND DISTANCE LEARNING - EKWUEME, Loveth Ogoegbunam; Oluwaseun, Babarotimi Opeyemi; AJIE, Ifeoma Abigail; OFODU, Patricia Ngozi; Ambrose, Smart Eromosele (Indonesian Journal of Library and Information Science, 2024)
This study investigates the impact of Fifth Industrial Revolution (5th IR) technologies on enhancing diversity and inclusive services in Open and Distance Learning libraries. Using a descriptive design, the research focused on librarians at the National Open University of Nigeria, with data collected through a Google Form questionnaire. Analysis was conducted using SPSS and linear regression to test hypotheses. Findings revealed that librarians believe 5th IR technology improves data extraction, processing, and service efficiency (mean score 3.44, SD = 0.586). The study identifies key implementation strategies, including awareness-raising, curriculum updates, training, collaboration, and skill enhancement. It emphasizes the importance of funding, reliable power supply, and collaboration for effective 5th IR adoption. The study underscores the potential for human-machine partnerships to automate tasks and foster connectivity, suggesting an optimistic outlook for the 5th IR’s role in promoting inclusive, customized library services in academic and distance learning environments.